Livestock in the Upper Euphrates Region - Al-Ani, Kamal S. Kazkoz; Al-Zobaie, Othman M. Naji (Al-Adab Journal, 2023)
Animal production is the second part of agricultural activity for any country as it constitutes an economic return, in addition to being a basic food for the population, in addition to the availability of a raw material for industry (%23,2) of the area of Anbar Governorate, and (%7.4) of the area of Iraq, and the area of arable and actually cultivated lands reached (232060) dunums, and the actually cultivated area was (148,232) dunums, and the percentage amounted to (% 63,87) of the total area The study showed the effect of natural and human geographical factors on the spatial variance of livestock. As for the geographical distribution of livestock, sheep came first with (181594) heads out of the total livestock in the region, and goats ranked second with (55,660) heads. While cows came in third place with (17466) heads, camels ranked fourth with (1840), and buffalo came in last place with (438), and then give a picture of the problems facing livestock and sweets The proposed solutions to these problems and the development of ways to advance the reality of livestock.